2011
DOI: 10.1016/j.virol.2010.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an NTPase motif in classical swine fever virus NS4B protein

Abstract: Classical swine fever (CSF) is a highly contagious and often fatal disease of swine caused by CSF virus (CSFV), a positive-sense single-stranded RNA virus within the Pestivirus genus of the Flaviviridae family. Here, we have identified conserved sequence elements observed in nucleotide-binding motifs (NBM) that hydrolyze NTPs within the CSFV non-structural (NS) protein NS4B. Expressed NS4B protein hydrolyzes both ATP and GTP. Substitutions of critical residues within the identified NS4B NBM Walker A and B moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
1
16
1
Order By: Relevance
“…NS4B also harbors a nucleoside triphosphatase (NTPase) motif. The NTPase activity is an absolute requirement for CSFV replication, but there is no evidence yet that modulating the NTPase activity may affect virulence (10). The 2 amino acids of NS4B identified in the present study are not located within the NTPase motif but clearly determine the replication efficiency of the virus in vivo and in vitro.…”
Section: Figcontrasting
confidence: 51%
See 2 more Smart Citations
“…NS4B also harbors a nucleoside triphosphatase (NTPase) motif. The NTPase activity is an absolute requirement for CSFV replication, but there is no evidence yet that modulating the NTPase activity may affect virulence (10). The 2 amino acids of NS4B identified in the present study are not located within the NTPase motif but clearly determine the replication efficiency of the virus in vivo and in vitro.…”
Section: Figcontrasting
confidence: 51%
“…This is reflected in numerous reports in which mutations of different functional domains in the structural proteins C, E rns , E1, and E2 and in the nonstructural proteins p7 and NS4B were shown to reduce the pathogenicity in pigs, indicating that these genes may be involved in determining CSFV virulence (7,8,9,10,11,12,13,32,36,37,38,39,40,46,54).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To further confirm the substrate preference of Atu5117, the kinetic parameters of Atu5117 for eight (d)NTPs were measured. We compared the kinetic parameters of Atu5117 (d)NTPase with those of other (d)NTPases [25][26][27][28][29]. The kinetic parameters of (d)NTPase for different nucleotide substrates were determined by analyzing the effects of substrate concentrations on hydrolysis rates.…”
Section: Kinetic Analysis and Substrate Specificity Of Atu5117 (D)ntpasementioning
confidence: 99%
“…NS4B contains two conserved domains, Walkers A (aa 209–216) and B (aa 335–342). Walker A exhibits NTPase activity and is essential for RNA replication [ 46 ]. Analysis of simple modular architecture research tool (SMART) has revealed that NS4B contains a Toll/interleukin-1 receptor (TIR)-like domain, and mutations in the TIR-like domain of NS4B significantly attenuate the virulence of CSFV in pigs [ 47 ].…”
Section: Modulation Of Viral Genomic Replication and Translation Bmentioning
confidence: 99%